Safety, tolerability, and efficacy of fasudil in amyotrophic lateral sclerosis (ROCK-ALS): a phase 2, randomised, double-blind, placebo-controlled trial - Koch, Jan Christoph; Leha, Andreas; Bidner, Helen; Cordts, Isabell; Dorst, Johannes; Günther, René; Zeller, Daniel; Braun, Nathalie; Metelmann, Moritz; Corcia, Philippe; De La Cruz, Elisa; Weydt, Patrick; et al. (The lancet, 2024)
Background - Fasudil is a small molecule inhibitor of Rho-associated kinase (ROCK) and is approved for the treatment of subarachnoid haemorrhage. In preclinical studies, fasudil has been shown to attenuate neurodegeneration, modulate neuroinflammation, and foster axonal regeneration. We aimed to investigate the safety, tolerability, and efficacy of fasudil in patients with amyotrophic lateral sclerosis. - Methods - ROCK-ALS was a phase 2, randomised, double-blind, placebo-controlled trial conducted at 19 amyotrophic lateral sclerosis centres in Germany, France, and Switzerland. Individuals (aged 18-80 years) with at least probable amyotrophic lateral sclerosis (as per the revised El Escorial criteria), a disease duration of 6-24 months, and a slow vital capacity greater than 65% of predicted normal were eligible for inclusion. Patients were randomly assigned (1:1:1) to receive 30 mg (15 mg twice daily) or 60 mg (30 mg twice daily) fasudil or matched placebo intravenously for 20 days over a 4-week period. Follow-up assessments were performed at 45, 90, and 180 days after treatment initiation. The co-primary endpoints were safety until day 180 (defined as the proportion without drug-related serious adverse events) and tolerability during the treatment period (defined as the proportion who did not discontinue treatment due to suspected drug-related adverse events). The primary analyses were carried out in the intention-to-treat population, which included all participants who entered the treatment phase. This trial is registered at ClinicalTrials.gov (NCT03792490) and Eudra-CT (2017-003676-31) and is now completed. - Findings - Between Feb 20, 2019, and April 20, 2022, 120 participants were enrolled and randomised; two individuals assigned fasudil 30 mg withdrew consent before the baseline visit. Thus, the intention-to-treat population comprised 35 in the fasudil 30 mg group, 39 in the fasudil 60 mg group, and 44 in the placebo group. The estimated proportion without a drug-related serious adverse event was 1·00 (95% CI 0·91 to 1·00) with placebo, 1·00 (0·89 to 1·00) with fasudil 30 mg, and 1·00 (0·90 to 1·00) with fasudil 60 mg; the difference in proportions was 0·00 (95% CI -0·11 to 0·10; p>0·99) for fasudil 30 mg versus placebo and 0·00 (-0·10 to 0·10; p>0·99) for fasudil 60 mg versus placebo. Treatment tolerability (the estimated proportion who did not discontinue) was 0·93 (95% CI 0·81 to 0·99) with placebo, 1·00 (0·90 to 1·00) with fasudil 30 mg, and 0·90 (0·76 to 0·97) with fasudil 60 mg; the difference in proportions was 0·07 (95% CI -0·05 to 0·20; p=0·25) for fasudil 30 mg versus placebo, and -0·03 (-0·18 to 0·10; p=0·70) for fasudil 60 mg versus placebo. Eight deaths occurred: two in the placebo group, four in the fasudil 30 mg group, and two in the fasudil 60 mg group. The most common serious adverse events were respiratory failure (seven events), gastrostomy (five events), pneumonia (four events), and dysphagia (four events). No serious adverse events or deaths were attributed to study treatment. Adverse events, which were mainly related to disease progression, occurred in 139 participants in the placebo group, 108 in the fasudil 30 mg group, and 105 in the fasudil 60 mg group. - Interpretation - Fasudil was well tolerated and safe in people with amyotrophic lateral sclerosis. The effect of fasudil on efficacy outcomes should be explored in larger clinical trials with a longer treatment duration, oral administration, and potentially higher dose of the trial drug. - Funding - Framework of the E-Rare Joint Transnational Call 2016 “Clinical research for new therapeutic uses of already existing molecules (repurposing) in rare diseases”.
Online verfügbar: 16. Oktober 2024, Artikelversion: 16. Oktober 2024
Gesehen am 25.05.2025